Derived equivalence, recollements under $ H $-Galois extensions - Dong, Jinlei; Li, Fang; Sun, Longgang (AIMS mathematics, 2023)
In this paper, assume that $ H $ is a Hopf algebra and $ A/B $ is an $ H $-Galois extension. Firstly, by introducing the concept of an $ H $-stable tilting complex $ T_{\bullet} $ over $ B $, we show that $ T_{\bullet}\otimes_BA $ is a tilting complex over $ A $ and a derived equivalence between two $ H $-module algebras can be extended to smash product algebras under some conditions. Then we observe that $ 0→ {\rm End}_{\mathcal{D}^b(B)}(T_{\bullet})→ {\rm End}_{\mathcal{D}^b(A)}(T_{\bullet}\otimes_BA) $ is an $ H $-Galois Frobenius extension if $ A/B $ is an $ H $-Galois Frobenius extension. Finally, for any perfect recollement of derived categories of $ H $-module algebras, we apply the above results to construct a perfect recollement of derived categories of their smash product algebras and generalize it to $ n $-recollements.